2015
DOI: 10.1016/j.adaj.2015.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Association of periodontitis and human papillomavirus in oral rinse specimens

Abstract: Background-Human papillomavirus (HPV) positive oropharyngeal squamous cell carcinomas are increasing in incidence and are becoming significant public health concerns. Periodontitis is a chronic condition in which the affected tissue may facilitate oral HPV infection and persistence. The purpose of this study was to determine if an association of the presence of HPV in oral rinse specimens and periodontal disease exists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 34 publications
5
17
3
Order By: Relevance
“…Taken together, we found that the Han nationality, average monthly income, and the time needed to reach the nearest town hospital have significant effects on health care-seeking delay and proved that the accessibility of health services may affect health care-seeking behavior [ 36 , 37 , 38 ]. However, we did not find a strong link between sex, age, and literacy, and treatment delay, somewhat at variance with other studies [ 39 , 40 , 41 , 42 , 43 , 44 ]. It is worth noting that we should strengthen TB control in remote areas, particularly the areas with unsound medical systems.…”
Section: Discussioncontrasting
confidence: 89%
“…Taken together, we found that the Han nationality, average monthly income, and the time needed to reach the nearest town hospital have significant effects on health care-seeking delay and proved that the accessibility of health services may affect health care-seeking behavior [ 36 , 37 , 38 ]. However, we did not find a strong link between sex, age, and literacy, and treatment delay, somewhat at variance with other studies [ 39 , 40 , 41 , 42 , 43 , 44 ]. It is worth noting that we should strengthen TB control in remote areas, particularly the areas with unsound medical systems.…”
Section: Discussioncontrasting
confidence: 89%
“…In this study, HPV DNA was easily detected in the healthy population in cells obtained from apparently normal oral mucosa using an average of 50 ng genomic DNA, as suggested by [14]. Moreover, according to these results, specimens collected using brush cytology resulted as good as those obtained using oral gargle, since the prevalence of oral HPV infection remained almost identical to that reported in other studies [11,[15][16][17]. Any oral exfoliative cytological procedure capable of reducing false negative or false positive results would support the method as a more effective tool to screen for oral pre-cancer or cancer lesion, and for other specific viral diseases; the finding that recent tooth-brushing increases HPV detection also suggests that the current sampling techniques may be improved by epithelial scraping [18] Recent studies suggest that oral HPV prevalence is substantially lower than genital HPV infection (D'Souza et al and Read et al) and greatly fluctuating in normal oral mucosa because of differences in sample types, sample collection methods, sample quantitation, level of sensitivity, PCR primer specificity and/or presence of PCR inhibitors [14,19].…”
Section: Discussionsupporting
confidence: 82%
“…It has been speculated that an inflamed periodontal pocket serves as a reservoir for HPV and induces HPV infection (19). Whether periodontal disease is related to oral HPV infection remains controversial (20)(21)(22), though the presence of such inflammatory diseases may serve an important role in the biology of HPV infection. On the other hand, HPV may be involved in deterioration associated with periodontal disease (i.e., increased alveolar bone loss) in accordance with other pathogenic factors (18).…”
Section: Discussionmentioning
confidence: 99%